(untitled) (Indian Forester, 1944)
The Central Silviculturist has sent us the following account of an experiment carried out in the Bori forests by the Divisional Forest Officer, Hoshangabad, on the effect of the diameter of teak stumps on survival percentage and height growth. The experiment is of interest in that it confirms the results of the original experiments in Madras. It is noticed that the design of the experiment is symmetrical and modern practice is the avoidance of any lay-out with a tendency to bias. The relatively small height growth at the end of the first growing season is probably due to late planting, vis, June 21st, and to an abrupt termination of the monsoon. Stumps over half an inch in diameter show an increased survival percentage of 15 per cent and an increased height growth of over 100 per cent. Compared with stumps of smaller diameter.